Dialogues ou monologues ? Les dialogues polémiques catholiques à l’épreuve des guerres de religion. Les exemples de Jean Gacy, Artus Désiré et Simon Poncet - Anne-Gaëlle Leterrier Gagliano (Caliban: French Journal of English Studies)
At first sight, polemical dialogues imply a confrontation between two opposed views. However, the Catholic authors who took up that genre during the French Wars of Religion used Reformed theses as a simple starting point to develop and defend the Catholic doctrine. These authors sought primarily to fortify their readers in their faith and their goal was not to introduce them to heterodox discourses. First Jean Gacy (1525), then Artus Désiré (1550-1570,)and finally Simon Poncet (c.1589) all exemplify such a closed debate, for the benefit of a Catholic community that had to be reunited. The space of the dispute is thus a closed space or, in other words, a space which seems to include the Other, who is in fact only introduced to be defeated or excluded, in order to bolster the confidence of the Catholics that the final victory of the Church was at hand.